Additive manufacturing for COVID-19: devices, materials, prospects, and challenges. (September 2020) - Advincula, Rigoberto C.; Dizon, John Ryan C.; Chen, Qiyi; Niu, Ivy; Chung, Jason; Kilpatrick, Lucas; Newman, Reagan
Abstract : Abstract: The current COVID-19 pandemic has caused the shortage of personal protective equipment (PPE) where improvised manufacturing in particular 3D printing has addressed many needs. This prospective discusses the current global crisis, then follows the wide interest in addressing the shortage of medical devices and PPEs used for treatment and protection against pathogens. An overview of the 3D printing process with polymer materials is given followed by the different 3D printing projects of PPEs and medical devices that emerged for the pandemic (including validation/testing). The potential for rapid prototyping with different polymer materials and eventual high-throughput production is emphasized.